Liquefaction-induced emission enhancement of tetraphenylethene derivatives. Issue 15 (8th February 2017) - Machida, Takashi; Taniguchi, Ryosuke; Oura, Tsuyoshi; Sada, Kazuki; Kokado, Kenta
Abstract : A typical AIE dye, TPE, was liquefied by attaching long and branched alkyl chains. The obtained liquid dye showed intense emission compared to that of the solid dye or TPE. The linkage between TPE and the alkyl chain led to significant differences in their photoluminescent and thermal properties. Abstract : A typical AIE dye, TPE, was liquefied by attaching long and branched alkyl chains. The obtained liquid dye showed intense emission compared to the solid dye or TPE. The linkage between TPE and the alkyl chain led to significant difference in their photoluminescent and thermal properties.